Modelling future climate change impacts on grapevine water requirements and growing cycle in three wine PDOs of NE Spain - Inmaculada Funes Mesa; Elisenda Sánchez-Costa; Xavier Aranda; Vicent Altava-Ortiz; Antoni Barrera-Escoda; Marc Prohom; Rafael Poyatos; Antoni Sánchez-Ortiz; Robert Savé; Felicidad de Herralde (OENO One)
Climate change is expected to heavily impact agriculture in the Mediterranean region due to higher temperatures and droughts. Within the agricultural systems, vineyards are one of the most affected by climate. Here we provide a diagnosis of the main impacts of climate change in three protected designations of origin (PDOs) in Catalonia (NE Spain) in the 21st century. This is fundamental for assessing the future suitability of grapevine cultivation in the study area. For this purpose, we estimated the annual net water needs of the vineyard and a set of agroclimatic parameters of crop phenology and ripening. Climate change impacts were estimated at 1 km pixel resolution using temperature and precipitation projections based on the IPCC AR5 RCPs 4.5 and 8.5 climate change scenarios. Water needs would be 2 to 3 times greater than current water needs and a general advance and shortening of the ‘Budburst to Harvest’ period were estimated. The flowering date would advance from 3 to 6 weeks and the harvest from 1 to 2.5 months, resulting in a duration of the ‘Budburst to Harvest’ period from 10 to 80 days shorter. Changes in temperature during ripening were also estimated. Minimum temperature and daily thermal amplitude during ripening could increase from 1.4 to 2.9 °C and from 0.4 to 2.8 °C, respectively, by the end of the century. Additionally, the number of tropical nights (nights with T min > 20 °C) at ripening would increase from 2 to 23.7 days during the second half of the 21st century. Dynamics would be similar in the three PDOs studied although the magnitude of impact would differ, leading, in some cases, to significant limitations for grapevine cultivation and wine production if no adaptation strategies are applied in the near future. Increases in water needs were slightly greater in Empordà PDO, while the potential impact on crop phenology and grapevine quality was greater in the Pla de Bages PDO. These results, despite the limitations from simplified methods, incomplete data and unaddressed uncertainties, could serve as a basis for the design of specific adaptation strategies to improve and maintain vineyards in the PDOs studied and could be extrapolated to similar PDOs and regions.